Central nervous system regulation of hepatic lipid and lipoprotein metabolism. Issue 1 (February 2017) - Taher, Jennifer; Farr, Sarah; Adeli, Khosrow
Abstract : Supplemental Digital Content is available in the text Abstract : Purpose of review: Hepatic lipid and lipoprotein metabolism is an important determinant of fasting dyslipidemia and the development of fatty liver disease. Although endocrine factors like insulin have known effects on hepatic lipid homeostasis, emerging evidence also supports a regulatory role for the central nervous system (CNS) and neuronal networks. This review summarizes evidence implicating a bidirectional liver–brain axis in maintaining metabolic lipid homeostasis, and discusses clinical implications in insulin-resistant states. Recent findings: The liver utilizes sympathetic and parasympathetic afferent and efferent fibers to communicate with key regulatory centers in the brain including the hypothalamus. Hypothalamic anorexigenic and orexigenic peptides signal to the liver via neuronal networks to modulate lipid content and VLDL production. In addition, peripheral hormones such as insulin, leptin, and glucagon-like-peptide-1 exert control over hepatic lipid by acting directly within the CNS or via peripheral nerves. Central regulation of lipid metabolism in other organs including white and brown adipose tissue may also contribute to hepatic lipid content indirectly via free fatty acid release and changes in lipoprotein clearance. Summary: The CNS communicates with the liver in a bidirectional manner to regulate hepatic lipid metabolism and lipoprotein production. Impairments in these pathways may contribute to dyslipidemia and hepatic steatosis in insulin-resistant states. Video abstract: http://links.lww.com/COL/A13